2019
DOI: 10.1111/phn.12615
|View full text |Cite
|
Sign up to set email alerts
|

Policy analysis of access to and reimbursement for nonpharmacologic therapies for cancer‐related fatigue

Abstract: Cancer‐related fatigue (CRF) is an important public health issue that involves millions of community‐dwelling cancer survivors. CRF is the most debilitating patient reported symptom related to cancer therapies and exacts a significant economic and social toll. It adversely impacts patients' work, social relationships, and overall quality of life. CRF prevalence ranges from 30% to 90% during therapy and often persists months and years afterwards. This policy analysis examines the problem of lack of patient acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…CCRF is often accompanied by distress, interferes with daily activities and social relationships, and limits patient's quality of life . In addition, CCRF is an important public health issue that incurs medical and societal costs …”
Section: Introductionmentioning
confidence: 99%
“…CCRF is often accompanied by distress, interferes with daily activities and social relationships, and limits patient's quality of life . In addition, CCRF is an important public health issue that incurs medical and societal costs …”
Section: Introductionmentioning
confidence: 99%
“…( 33 ) found that physical activity in patients with cancer was closely related to decreased fatigue. Fatigue is one of the most common and unmanageable symptoms in patients with cancer, with an incidence rate of 30%–99% ( 34 , 35 ). Patients with fatigue have a self-perceived depletion of energy and stamina, and decreased interest in exercise leads to reduced physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of CRF prevalence have been reported to range from 30% to 99%. 2 , 3 CRF affects patients' personal, social, and work lives and has profoundly negative effects on overall quality of life. 4 , 5 Despite the high prevalence of fatigue and its substantial influence on quality of life, routine screening of patients with cancer for fatigue and guidance for fatigue management has not received adequate attention in China.…”
Section: Introductionmentioning
confidence: 99%